Sarah Hibberd and Richard Wrigley, eds. 2014. Art, Theatre, and Opera in Paris, 1750-1850: Exchanges and Tensions - Doe, Julia (Current Musicology, 2021)
The eleven essays in this volume were produced for an interdisciplinary conference, “Correspondances: Exchanges and Tensions between Art, Theatre, and Opera in France, c. 1750–1850,” held at the National Gallery, London in the spring of 2010. This event coincided with an exhibition of the history paintings of Paul Delaroche. The artist’s purportedly “theatrical” style, and longstanding engagement with the theater more broadly, serve as a fitting starting point for a series of explorations of the interplay between the visual arts and the Parisian stage during the late-eighteenth and early-nineteenth centuries.